2022
DOI: 10.2196/37938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cybersickness Caused by Head-Mounted Display–Based Virtual Reality on Physiological Responses: Cross-sectional Study

Abstract: Background Although more people are experiencing cybersickness due to the popularization of virtual reality (VR), no official standard for the cause and reduction of cybersickness exists to date. One of the main reasons is that an objective method to assess cybersickness has not been established. To resolve this, research on evaluating cybersickness with physiological responses that can be measured in real time is required. Since research on deriving physiological responses that can assess cybersic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Meanwhile Silva et al [31] pointed out that although an exergame training session and a conventional training session both resulted in similar acute effects on Heart Rate and Blood Pressure, their results differed from those of this study in that systolic blood pressure decreased significantly immediately after the session. This result was also arrived at by Kim et al [53], in the case of people who had suffered cybersickness after using IVR. In our case, where we used a boxing application, the increase in post-intervention blood pressure may have been due to the overall movement demands, which could have been more physically demanding for our sample.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Meanwhile Silva et al [31] pointed out that although an exergame training session and a conventional training session both resulted in similar acute effects on Heart Rate and Blood Pressure, their results differed from those of this study in that systolic blood pressure decreased significantly immediately after the session. This result was also arrived at by Kim et al [53], in the case of people who had suffered cybersickness after using IVR. In our case, where we used a boxing application, the increase in post-intervention blood pressure may have been due to the overall movement demands, which could have been more physically demanding for our sample.…”
Section: Discussionsupporting
confidence: 73%
“…In any case, our results did not allow us to verify whether the presence of severe cybersickness symptoms would produce variations in the physiological parameters studied, nor whether a certain stability in these guarantees the absence of cybersickness, aspects to be evaluated in future studies. It is possible that the non-generation of cybersickness symptoms in our case is due to the fact that the exergame used does not lead to a conflict in the sample between its vestibular system and its visual perception of body movement [53].…”
Section: Discussionmentioning
confidence: 94%
“…As a result, it was found that the HR increased as the symptom scores increased, and the HRV was higher for the sickness group. Kim et al (2022) presented VR content to 16 subjects, performed an SSQ survey, and measured the biosignals (blood pressure, cortisol, and HR) before and after viewing of the content [18]. It was found that the HR and cortisol levels were greatly increased in subjects who experienced cybersickness.…”
Section: Discussionmentioning
confidence: 99%
“…Most changes that occur are generally related to the autonomic nervous system, such as increased heart rate frequency, body temperature, and blood pressure. Although an increase in heart rate is frequently associated with an increase in blood pressure, in a study conducted by Kim et al (2022), the participants' blood pressure actually decreased. This is due to a mismatch in perceptions generated by the vestibular system and the visual system in the central nervous system.…”
Section: Introductionmentioning
confidence: 92%
“…The human body that experiences cybersickness symptoms will respond by changing physiologically because it considers the use of immersive technology as a new stressor. According to Kim et al (2022) there is a relationship between the occurrence of cybersickness and changes in physiological responses to the use of VR. Most changes that occur are generally related to the autonomic nervous system, such as increased heart rate frequency, body temperature, and blood pressure.…”
Section: Introductionmentioning
confidence: 99%